Stargazin Dephosphorylation Mediates Homeostatic Synaptic Downscaling of Excitatory Synapses - Louros, Susana R.; Caldeira, Gladys L.; Carvalho, Ana Luísa (Frontiers in Molecular Neuroscience, 2018)
Synaptic scaling is a form of homeostatic plasticity that is critical for maintaining neuronal activity within a dynamic range, and which alters synaptic strength through changes in postsynaptic AMPA-type glutamate receptors. Homeostatic scaling down of excitatory synapses has been shown to occur during sleep, and to contribute to synapse remodeling and memory consolidation, but the underlying mechanisms are only partially known. Here, we report that synaptic downscaling in cortical neurons is accompanied by dephosphorylation of the transmembrane AMPA receptor regulatory protein stargazin, and by an increase in its cell surface mobility. The changes in stargazin surface diffusion were paralleled by an increase in the mobility of GluA1-containing AMPA receptors at synaptic sites. In addition, stargazin dephosphorylation was required for the downregulation of surface levels of GluA1-containing AMPA receptors promoted by chronic elevation of neuronal activity, specifically by mediating the interaction with the adaptor proteins AP-2 and AP-3A. Disruption of the stargazin-AP-3A interaction was sufficient to prevent the decrease in cell surface GluA1-AMPA receptor levels associated with chronically enhanced synaptic activity, suggesting that scaling down is accomplished through decreased AMPA receptor recycling and enhanced lysosomal degradation. Thus, synaptic downscaling is associated with both increased stargazin and AMPA receptor cell surface diffusion, as well as with stargazin-mediated AMPA receptor endocytosis and lysosomal degradation.